2021
DOI: 10.1016/j.crphar.2021.100039
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with terbutaline increases glucose and oleic acid oxidation and protein synthesis in cultured human myotubes

Abstract: Objective In vivo studies have reported several beneficial metabolic effects of β-adrenergic receptor agonist administration in skeletal muscle, including increased glucose uptake, fatty acid metabolism, lipolysis and mitochondrial biogenesis. Although these effects have been widely studied in vivo , the in vitro data are limited to mouse and rat cell lines. Therefore, we sought to discover the effects of the β 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…2019; Skagen et al . 2021) and clinical trials aiming to assess the applicability of selective beta 2 ‐agonists in lifestyle diseases such as obesity and type 2 diabetes, as well as muscle atrophic conditions (patent no: WO2005072714A1, ClinicalTrials.gov Identifier: NCT03005717.23‐25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019; Skagen et al . 2021) and clinical trials aiming to assess the applicability of selective beta 2 ‐agonists in lifestyle diseases such as obesity and type 2 diabetes, as well as muscle atrophic conditions (patent no: WO2005072714A1, ClinicalTrials.gov Identifier: NCT03005717.23‐25).…”
Section: Introductionmentioning
confidence: 99%
“…These effects include muscle growth (Hostrup et al 2015;Jessen et al 2018), slow-to-fast twitch muscle fibre type transition (Hostrup et al 2018a), lipolysis (Onslev et al 2019), and alterations of numerous proteins involved in cellular metabolism (Hostrup et al 2018a,b). This has made the beta 2 -adrenergic receptor an emerging area in pharmaceutical drug development, with ongoing pre-clinical (Koziczak-Holbro et al 2019;Skagen et al 2021) and clinical trials aiming to assess the applicability of selective beta 2 -agonists in lifestyle diseases such as obesity and type 2 diabetes, as well as muscle atrophic conditions (patent no: WO2005072714A1, ClinicalTrials.gov Identifier: NCT03005717. [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, noradrenaline increased mitochondrial network mass and size, most likely by increased mitochondrial turnover, as evidenced by increased mitophagy. Several studies have found that catecholamine-induced stimulation of β-adrenergic receptors promotes mitochondrial biogenesis in both skeletal muscle [ 32 , 33 ] and other tissues [ 34 , 35 ]. In keeping with this, noradrenaline significantly increased mitochondrial content what we confirmed by three independent techniques.…”
Section: Discussionmentioning
confidence: 99%